MOBILITAS SOSIAL PETANI KARET KE PERTAMBANGAN EMAS TANPA IZIN DI DESA KOTO TUO KECAMATAN BATANG PERANAP KABUPATEN INDRAGIRI HULU - Ardiansyah "; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The location of the research is the village of Koto Tuo District of Batang Peranap Indragiri Hulu. Considerations for selecting the location of this study was due to gold mining is an illegal job without permission is prohibited, when compared to the work of farmers and others. The researchers aimed to describe and mencarari information about job mobility:1. To know anyone who did the mobility of livelihood in the village of Koto Tuo District of Batang Peranap2. What factors are encouraging the mobility of livelihood in the village of Koto Tuo District of Batang Peranap3. What type of mobility that occurred in the village of Koto Tuo District of Batang PeranapThe population in this study were people who did Mobility Works of non-miners into the gold peambang 120 people. In determining the sample taken as many as 30% of the 120 respondents ie 36 people.According to the research going on aspects of mobility in research location by driving factors such as economic conditions of the respondents were small and the individual condition of the respondent, and the orientation factor attitude that wants to improve the prospects for social mobility and the promising results of the work.Keywords : Mobility Occupation, Farmer Rubber, Illegal.